1994
DOI: 10.1021/ac00081a008
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Determination of Proteins by Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry

Abstract: A method of protein quantitative analysis using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry is described. To decouple the quantitative approach from the extreme dependence of absolute ion signal on the experimental parameters of the matrix-assisted technique, the method relies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
105
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(107 citation statements)
references
References 14 publications
2
105
0
Order By: Relevance
“…The main characteristics and applications of MALDI TOF-MS have been presented in some review articles. [27][28][29][30][31][32][33][34][35] Recent works dealing with the use of the technique to the identification and structural analysis of various compounds can be mentioned. [36][37][38][39][40][41][42][43][44][45][46][47][48] Coupling of MALDI with liquid chromatography, capillary electrophoresis (CE) and gel chromatography is a way to extend its applicability.…”
Section: An Overview Of Analytical Applications Of Tof-ms Analyzersmentioning
confidence: 99%
“…The main characteristics and applications of MALDI TOF-MS have been presented in some review articles. [27][28][29][30][31][32][33][34][35] Recent works dealing with the use of the technique to the identification and structural analysis of various compounds can be mentioned. [36][37][38][39][40][41][42][43][44][45][46][47][48] Coupling of MALDI with liquid chromatography, capillary electrophoresis (CE) and gel chromatography is a way to extend its applicability.…”
Section: An Overview Of Analytical Applications Of Tof-ms Analyzersmentioning
confidence: 99%
“…It relies on co-crystallizations of trace analytes with matrix compounds, but the typical sample morphology and spatial distribution of analytes are highly irregular. The heterogeneous analyte distributions result in poor data reproducibility [2,6,7] and make quantification analysis with MALDI mass spectrometry (MS) difficult [8]. The reasons for a heterogeneous spatial distribution of molecules, or heterogeneity defined hereafter, may involve multiple factors during droplet drying processes, such as physical properties of solutes [9], viscosity of solutions [10], and hydrodynamic flows inside droplets [11].…”
Section: Introductionmentioning
confidence: 99%
“…In the work of Nelson et al [1], where MALDI-TOF was used for protein quantification, their results demonstrated a linear relationship of molecular ion signals to the concentration of protein in solution. This method used the normalization of analyte molecular ion signals to the signals of internal reference molecular ions.…”
mentioning
confidence: 98%
“…The principal activity in this area has been reported by Nelson et al [1] as well as by Hercules et al [2][3][4][5][6]. In their studies, proteins and peptides were analyzed and the intensities of single peaks were considered.…”
mentioning
confidence: 99%